Influenza Vaccination in the Face of Immune Exhaustion: Is Herd Immunity Effective for Protecting the Elderly?. (29th January 2012) - Lang, Pierre Olivier; Samaras, Dimitrios; Samaras, Nikolaos; Govind, Sheila; Aspinall, Richard
Abstract : At the start of the 21st century, seasonal influenza virus infection is still a major public health concern across the world. The recent body of evidence confirms that trivalent inactivated influenza vaccines (TIVs) are not optimal within the population who account for approximately 90% of all influenza-related death: elderly and chronically ill individuals regardless of age. With the ever increasing aging of the world population and the recent fears of any pandemic influenza rife, great efforts and resources have been dedicated to developing more immunogenic vaccines and strategies for enhancing protection in these higher-risk groups. This paper describes the mechanisms that shape immune response at the extreme ages of life and how they have been taken into account to design more effective immunization strategies for these vulnerable populations. Furthermore, consideration will be given to how herd immunity may provide an effective strategy in preventing the burden of seasonal influenza infection within the aged population.